2021
DOI: 10.1016/j.vaccine.2021.08.058
|View full text |Cite
|
Sign up to set email alerts
|

Public attitudes toward COVID-19 vaccines on English-language Twitter: A sentiment analysis

Abstract: Objective To identify themes and temporal trends in the sentiment of COVID-19 vaccine-related tweets and to explore variations in sentiment at world national and United States state levels. Methods We collected English-language tweets related to COVID-19 vaccines posted between November 1, 2020, and January 31, 2021. We applied the Valence Aware Dictionary and sEntiment Reasoner tool to calculate the compound score to determine whether the sentiment mentioned in each tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
92
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(102 citation statements)
references
References 29 publications
7
92
0
3
Order By: Relevance
“…Yin et al [14] proposed a novel behavioral dynamics model on Weibo messages to analyze vaccine acceptance in China, and they demonstrated that Chinese individuals were inclined to be positive about side effects over time. Furthermore, many studies explored tweets related to COVID-19 vaccines to understand the evolution of public concerns and sentiments in different regions [15][16][17]. These studies mainly revealed that public concerns and sentiments on COVID-19 vaccines fluctuated with time and geography, and had strong correlations with some major events about COVID-19 vaccines.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Yin et al [14] proposed a novel behavioral dynamics model on Weibo messages to analyze vaccine acceptance in China, and they demonstrated that Chinese individuals were inclined to be positive about side effects over time. Furthermore, many studies explored tweets related to COVID-19 vaccines to understand the evolution of public concerns and sentiments in different regions [15][16][17]. These studies mainly revealed that public concerns and sentiments on COVID-19 vaccines fluctuated with time and geography, and had strong correlations with some major events about COVID-19 vaccines.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Several studies used Twitter as the source of data for their analysis [24,29,30,35]. Social media data, particularly geotagged tweets, are valuable and cost-effective resources for near real-time spatial and spatiotemporal analyses.…”
Section: Discussionmentioning
confidence: 99%
“…However, the Voronoi map (Theisen polygon) was utilized in only one study [23]. The contribution of 11 articles to the spatial analysis of COVID-19 vaccination was only limited to mapping [24][25][26][27][28][29][30][31][32][33][34]. Although most mapping studies disregarded time components, and used static presentation of data, temporal variations or transmission dynamics were mapped in [24,29,30,[35][36][37].…”
Section: Vaccine Mappingmentioning
confidence: 99%
See 1 more Smart Citation
“…Social media sentiment analysis allows agencies to examine public sentiment in a way that can help change public policy. For example, researchers analyzed Tweets about the COVID-19 vaccine to capture public perceptions so that future communications could be shaped to address prevalent concerns or misinformation [41]. In a study analyzing selected Twitter posts, Nemes and Kiss [42] found that sentiment toward COVID-19 was largely negative.…”
Section: Sentiment Analysis As a Measure Of People's Attitudesmentioning
confidence: 99%